2013
DOI: 10.17503/agrivita-2013-35-1-p054-063
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Agroforestry System in Maintaining Carbon Stocks and Reducing Emission Rate at Jangkok Watershed, Lombok Island

Abstract: Agroforestry systems under rules of communitybased forest management support local livelihoods in the Jangkok watershed, Lombok Island. One of the conditions from the forest authoritiesfor allowing agroforestry system is that it should maintain forest conditions. Since 1995 the Jangkok watershed has undergone rapid land use change, especially in the forest area. These changes led to a reduction of carbon stocks and thus to emission of CO2. This research aimed to: (1) Measure the carbon stocks in several land u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 7 publications
1
5
0
7
Order By: Relevance
“…According to [27], basal area of tree has a high correlation with total carbon stock. This is also corresoinding with [29], who reported that the decline in carbon stocks in the Jangkok watershed (Lombok Island) was closely related to a decrease in the number of large trees, reflecting a decrease in basal area of trees after the forest in the area was converted to agriculture. The carbon stored below the soil surface (7,549 tonnes ha -1 ) is greater in value than the carbon stored above the ground (4,096 tonnes ha -1 ) in Cikalong Wetan.…”
Section: The Average Of Carbon Stored In Each Carbon Poolsupporting
confidence: 84%
“…According to [27], basal area of tree has a high correlation with total carbon stock. This is also corresoinding with [29], who reported that the decline in carbon stocks in the Jangkok watershed (Lombok Island) was closely related to a decrease in the number of large trees, reflecting a decrease in basal area of trees after the forest in the area was converted to agriculture. The carbon stored below the soil surface (7,549 tonnes ha -1 ) is greater in value than the carbon stored above the ground (4,096 tonnes ha -1 ) in Cikalong Wetan.…”
Section: The Average Of Carbon Stored In Each Carbon Poolsupporting
confidence: 84%
“…In addition to improve the conservation of biodiversity, agroforestry systems also can enhance the ecosystem services provision. In example carbon stock and reduce net emission rates there also agroforestry system contribution (Markum, Ariesoesiloningsih, Suprayogo, & Hairiah, 2013). Santos, Crouzeilles, & Sansevero (2019) in their experiment showed that agroforestry systems provide more benefit of biodiversity and ecosystem services up to 45-65 % than conventional production system.…”
Section: Agroforestry Systems In Kulon Progo Based On the Structure Amentioning
confidence: 99%
“…Kawasan hutan ini telah mengalami perubahan tutupan hutan yang masif terjadi sejak tahun 2000 -2005 akibat penebangan illegal (Muktar, 2011). Sejalan dengan hal tersebut, berdasarkan hasil interpretasi Citra Landsat 5 TM di Kawasan tersebut, telah terjadi penurunan tutupan hutan primer sebanyak 22 % sejak 1995-2010 (Markum et al, 2013;Tratib, 2011). Perubahan tutupan hutan primer tersebut beralih menjadi hutan sekunder dengan beragam sistem penggunaan lahan, diantaranya adalah penggunaan sistem agroforestri.…”
Section: Pendahuluanunclassified